Respuesta :
Answer:
- 2a² - 8a + 6
Step-by-step explanation:
Given function:
- f(x) = 2x² - 2
To find f(2 - a) substitute x with 2 - a:
- f(2 - a) =
- 2(2 - a)² - 2 =
- 2(4 - 4a + a²) - 2 =
- 2a² - 8a + 8 - 2 =
- 2a² - 8a + 6
f(x)=2(x)^2-2
[tex]\\ \rm\hookrightarrow f(2-a)[/tex]
[tex]\\ \rm\hookrightarrow 2(2-a)^2-2[/tex]
[tex]\\ \rm\hookrightarrow 2(2^2-4a+a^2)-2[/tex]
[tex]\\ \rm\hookrightarrow 2(4-4a+a^2)-2[/tex]
[tex]\\ \rm\hookrightarrow 8-8a+2a^2-2[/tex]
[tex]\\ \rm\hookrightarrow 2a^2-8a+6[/tex]